Experimental and Numerical Investigation on Compression Orthotropic Properties of Spruce Wood in Axial and Transverse Loading Directions - Weizhou ZHONG; Alexis RUSINEK; Tomasz JANKOWIAK; Xicheng HUANG; Farid ABED (Engineering Transactions, 2015)
Compression tests on spruce wood in axial, radial and tangential directions have been performed using an INSTRON hydraulic machine. Spruce elastic mechanical properties and plastic deformation behaviour are presented. Experimental results allow to demonstrate different spruce failure modes: fibers buckling and collapsing are noticed under axial compression whereas, fibers slippage and delamination are the main failure modes under compression loading in radial and tangential directions. Spruce energy absorption efficiency and ideality energy absorption efficiency in the three loading directions are also analyzed. Representative volume element (RVE) model is adopted assuming transverse isotropic behavior to simulate wood microstructure in all directions. It was shown that micro-cell arrangement leads to wood macromechanical property spatial anisotropy. Porosity and hole shape effects on simulation results are estimated by RVE models with hexagon, circle, pentagon and square holes.